Pembelajaran daring pada masa pandemi COVID-19: Identifikasi kesulitan guru dan upaya mengatasinya pada mata pelajaran Geografi SMA Negeri - Sari, Dian Nofita; Rosyida, Fatiya; Insani, Nailul; Soekamto, Hadi (Universitas Negeri Malang, 2023)
Due to the COVID-19 pandemic, the government made a decision by conducting the learning process from home through online learning. This study aims to identify the difficulties of geography teachers in public high schools and efforts to overcome them in online learning during the COVID-19 pandemic. This research method is descriptive quantitative. The population of this study were 12 geography teachers of public high schools in Kediri Regency. Data collection techniques by distributing questionnaires in the form of a questionnaire. Data analysis used the percentage technique to compare the frequency of answers to questions in each category with the number of respondents. The results obtained with a score of 47 can be classified as having difficulty. Geography teachers in Kediri Regency have difficulty delivering material, managing classes, evaluating students, low internet mastery skills, low student readiness in online learning and inadequate student learning environment situations make it difficult for teachers to optimize the learning process. Efforts to overcome the teacher by participating in MGMP activities to increase information so that the implementation of online learning is more effective. Teachers can operate applications, improve communication with students and collaborate with parents face-to-face to optimize the achievement of learning objectives. Adanya pandemi COVID-19 pemerintah mengambil keputusan dengan melakukan proses pembelajaran dari rumah melalui pembelajaran daring. Penelitian ini bertujuan untuk mengidentifikasi kesulitan guru geografi SMA Negeri dan upaya mengatasinya pada pembelajaran daring saat masa pandemi COVID-19. Metode penelitian ini adalah deskriptif kuantitatif. Populasi penelitian ini adalah 12 guru geografi SMA Negeri di Kabupaten Kediri. Teknik pengumpulan data dengan menyebarkan kuesioner berupa angket. Analisis data menggunakan teknik persentase untuk membandingkan frekuensi jawaban pertanyaan tiap kategori dengan jumlah responden. Diperoleh hasil skor 47 dapat diklasifikasikan mengalami kesulitan. Guru geografi di Kabupaten Kediri mengalami kesulitan menyampaikan materi, mengelola kelas, mengevaluasi siswa, rendahnya kemampuan penguasaan internet, kesiapan siswa dalam pembelajaran daring yang rendah dan situasi lingkungan belajar siswa yang kurang memadai membuat guru kesulitan untuk mengoptimalkan proses pembelajaran. Upaya mengatasi yang dilakukan guru dengan mengikuti kegiatan MGMP untuk meningkatkan informasi agar pelaksanaan pembelajaran daring lebih efektif. Guru dapat mengoperasikan aplikasi, meningkatkan komunikasi dengan siswa dan bekerjasama dengan orang tua secara tatap muka untuk mengoptimalkan pencapaian tujuan pembelajaran.